Development of innovation house to improve the competence of developer teachers - Ari Widodo; Andi Suhandi; Eka Murdani (Jurnal Inovasi Pendidikan IPA, 2022)
The Innovation House program has been developed with the validation criteria of 'Very Good' based on expert judgment. The Innovation House was developed using the ADDIE method (Analysis, Design, Develop, Implement and Evaluate). The vision of the Innovation House is to prepare teacher developers as reflectors, problem solvers, and decision-makers in science learning. The Innovation House aims to improve science teachers' competence in developing curriculum, especially lesson planning (objectives, steps, and assessments). On average, 80% of the lesson plans made by teachers were by the content and constructs of the lesson plans, while at the beginning of the program, the average suitability of new content and constructs was about 56%, with an N-gain score of 0.5 or a moderate increase category. Based on the average assessment of RPP content and constructs, the Rumah Innovation Program effectively improves teacher competence in making Innovative RPP by increasing the aspects of reflection, problem-solving and decision making. The teacher participants' response during the programs was 'imposing' and gave a 'positive response' based on the attitude scale instrument.